2016
DOI: 10.1016/j.bjhh.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive study of the prevalence of anemia, hypertension, diabetes and quality of life in a randomly selected population of elderly subjects from São Paulo

Abstract: BackgroundThe rapid increase in the aged population has resulted in a growing number of cases of chronic diseases. This increase is an important demographic change that low- and middle-income countries have to face and poses a new challenge to health services. One of the first steps to formulate public policies is to understand the reality of each country's aging population. This study describes the prevalence of anemia, hypertension and diabetes and the overall health status in pre-elderly and elderly subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
3
0
2
Order By: Relevance
“…The incidence of hypertension is very high, especially in elderly patients over 60 years, with a prevalence of 60-80% per year in the entire elderly population. Research conducted in the Sao Paulo region, which discovered a prevalence of 70% among the elderly of the entire population, also supports this situation [5] .…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…The incidence of hypertension is very high, especially in elderly patients over 60 years, with a prevalence of 60-80% per year in the entire elderly population. Research conducted in the Sao Paulo region, which discovered a prevalence of 70% among the elderly of the entire population, also supports this situation [5] .…”
Section: Introductionmentioning
confidence: 78%
“…This result occurred because the women who had entered menopause had lower estrogen levels. This condition can lead to a decrease in HDL levels which function in maintaining healthy blood vessels by decreasing HDL levels and high LDL levels in the body, which can be at risk or can affect the occurrence of atherosclerosis which can increase blood pressure [5,10] . According to the findings of research conducted in the Public Health Center of Rendeng on the relationship between body mass index and the incidence of hypertension in elderly people, hypertension grade 1 had a percentage of (69.2 percent), and The Relationship between Body Mass Index and Smoking History on Incidence Rate of Hypertension in the Elderly 9 (2) Agust 2022 grade 2 had a significantly higher percentage, which was body mass index with the obesity category, which had a percentage level of (52.9 percent).…”
Section: Discussionmentioning
confidence: 99%
“…Keadaan ini didukung oleh penelitian yang menunjukkan bahwa prevalensi hipertensi meningkat seiring dengan pertambahan usia. Pada sebuah penelitian di Sao Paulo didapatkan prevalensi hipertensi pada lansia sebesar 70% dari jumlah populasinya (Lacerdaa, 2016). Keadaan serupa juga ditemukan pada penelitian yang dilakukan di China, dimana pada penelitian tersebut hipertensi ditemukan pada 53% populasi lansia (Miao, 2015).…”
Section: Hubungan Usia Dengan Kejadian Hipertensiunclassified
“…In another study performed in Sao Paulo, it was found that prevalence of hypertension among elderly groups was 70 % of the total population [16]. Research in China also shows that hypertension is found in 53 % of the elderly population [17].…”
mentioning
confidence: 95%